Public Health Literacy, Knowledge, and Awareness Regarding Antibiotic Use and Antimicrobial Resistance during the COVID-19 Pandemic: A Cross-Sectional Study - Suhaib M. Muflih; Sayer Al-Azzam; Reema A. Karasneh; Barbara R. Conway; Mamoon A. Aldeyab (MDPI AG, 2021)
Multi-drug-resistant (MDR) organisms pose a global threat to modern medicine, which has grown as a result of irrational antibiotic use and misuse. This study aimed to assess general public knowledge in Jordan and awareness of antibiotics and antibiotic resistance during the COVID-19 pandemic. A cross-sectional study was carried out utilizing the WHO multicountry public awareness survey. The study population was composed mainly of social media users, and a total of 1213 participants completed the online survey. According to the findings, more than half of the participants were well versed in antibiotic use and resistance. Those with adequate health literacy were found to better understand antibiotics (OR = 1.37, p = 0.017) and antibiotic resistance (OR = 1.46, p = 0.003). The vast majority (88.5%) recognized at least one antibiotic resistance term; however, 53.2% believed that antibiotic resistance is a problem in other nations. The participants in this study reported using antibiotics incorrectly, believing that they were treating sore throats, colds, and flu. The participants were well aware of antibiotic resistance solutions and their consequences on health. Age, education, health literacy, and antibiotic knowledge were found to be substantially (p < 0.05) associated with greater awareness of antibiotic resistance. The findings highlight the need for antimicrobial resistance education campaigns, health literacy, and antibiotic stewardship initiatives.